The Causality of Bank’s Health Rate Towards Sharia Banking Share Price in Indonesia - Muhammad Nasir; Muhammad Suuip; Rika Annisa; Yanti Hasbian Setiawati; Moh. Romli (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
This study aims to determine the causality relationship of financing to deposit ratio, good corporate governance, return on asset, and capital adequacy ratio toward sharia banking share price in Indonesia. Data used in this study are financial statements of Sharia banking companies and share price data from May 2018 to November 2020. The samples used are Bank Panin Dubai Syariah, Bank BRI Syariah, and Bank BTPN Syariah. The analysis model used is the Panel Vector Autoregression (PVAR) and performed with Eviews 10. The results found that financing to deposit ratio, good corporate governance, and return on assets have no causality relationship towards the share price. The capital adequacy ratio has a causality relationship towards the share price at a significant rate of 10%. The share price has a causality relationship towards the capital adequacy ratio. Financing to deposit ratio has a causality relationship towards good corporate governance. Return on assets has a causality relationship towards financing to deposit ratio. The change of sharia banking share price in the 12th month prediction was influenced by CAR is 3.32%, GCG is 0.42%, FDR is 0.32%, and ROA is 0.19%.